Metastasis-Initiating Cells in Renal Cancer - I. Khan, Mohammed; M. Czarnecka, Anna; Duchnowska, Renata; Kukwa, Wojciech; Szczylik, Cezary (Current Signal Transduction Therapy, 2013)
Metastasis is a complex process that propagates cells from the primary or initial site of the cancer occurrence to distant parts of the body. Cancer cells break from the cancer site and circulate through the bloodstream or lymph vessels, allowing them to reach nearly all parts of the body. These circulating tumour cells (CTCs) contain specialized metastasisinitiating cells (MICs) that reside in the biological heterogeneous primary tumour. Researchers have hypothesized that metastasis of renal cell carcinoma is initiated by circulation of MICs in patients’ blood and bone marrow. Based on the cancer stem/progenitor cell concept of carcinogenesis, understanding the molecular phenotypes of metastasis-initiating cells (MICs) in renal cancer could play a vital role in developing strategies for therapeutic interventions in renal cancer. Existence of MICs among CTCs in renal carcinoma has not been proven in large scale. However, some studies have reported that specialized markers are found on the surface of circulating cells from the primary tumour. In mice, MICs have been isolated from CTCs using such markers, which have then been transplanted into xenograft model to show whether they give rise to metastasis in different organs. Considering these findings, in this review we have attempted to summarize the studies connected with MICs and their gene expression profiles that are responsible for metastasis in renal cancer.
Keywords: metastasis-initiating cells